Electrochemical Hydrogen Storage in a Highly Ordered Mesoporous Carbon - Liu, Dan; Zeng, Chao; Tang, Haolin; Zheng, Dong; Li, Rong; Qu, Deyu; Xie, Zhizhong; Lei, Jiahen; Xiao, Liang; Qu, Deyang (Frontiers in Energy Research, 2014)
A highly ordered mesoporous carbon (HOMC) has been synthesized through a strongly acidic, aqueous cooperative assembly route. The structure and morphology of the carbon material were investigated using TEM, SEM, and nitrogen adsorption–desorption isotherms. The carbon was proven to be meso-structural and consisted of graphitic micro-domain with larger interlayer space. Active carbon impedance and electrochemical measurements reveal that the synthesized highly ordered mesoporous carbon (HOMC) exhibits a promoted electrochemical hydrogen insertion process and improved capacitance and hydrogen storage stability. The meso-structure and enlarged interlayer distance within the HOMC are suggested as possible causes for the enhancement in hydrogen storage. Both hydrogen capacity in the carbon and mass diffusion within the matrix were improved.